A Penyuluhan Efek Pemaparan Obat Nyamuk Bakar 10 Jam terhadap organ paru di Kampung Mariuk Desa Maripari Kabupaten Garut - SUGIAH; Gina Nafsa Mutmainna; N. Ai Erlinawati; Herlin Rusyani; Astari Nurisani (LP4M STIKes Karsa Husada Garut, 2022)
Indonesia includes a tropical climate and is very suitable as a habitat for mosquitoes to breed. Efforts made by the community to deal with mosquitoes, one of which is using 10-hour mosquito coils circulating in the market and nearby supermarkets, 10-hour mosquito coils are the people's choice which is very popular because they are easy to obtain and the price is very cheap when compared to mosquito sprays. or electric mosquito coils. This community service activity was carried out aiming to increase public knowledge about the dangers of excessive use of mosquito coils against human lung organs. This activity was carried out in Mariuk Village, Maripari Village, Sukawening-Garut District, involving 30 members of the PKK. The results of the evaluation showed that the participants' knowledge about the dangers of using 10-hour mosquito coils increased after the counseling was carried out.